Sediment source variation using REEs, Sr, and Nd isotopic compositions: a case study in MD05-2901, northwestern South China Sea - You, Chen-Feng; Liao, Wei-Lan; Huang, Kuo-Fang; Chung, Chuan-Hisung; Liu, Zhifei (Frontiers in Marine Science, 2024)
The South China Sea (SCS) is the largest marginal sea in the western Pacific, fed by large Asian rivers, characterized by substantial volumes of sediment derived from surrounding Asian continents and islands. This study utilizes the rare earth elements (REEs), Sr isotopes (87Sr/86Sr), and Nd isotopes (ƐNd) in detritus fractions of MD05-2901 sediments in northwestern SCS, to evaluate the relative contribution among the Mekong River, the Red River, the Pearl River, and rivers in SW Taiwan over the last 32 ka. This deep-sea core is located off the coast of central Vietnam, an upwelling region with only minor continental inputs, and this study is important for a better understanding of the main sources of terrigenous material and their temporal variations in the region. In addition, potential particle exchange is examined using the same proxies in the Fe-Mn oxyhydroxide fractions. The obtained records are systematically compared with the available climatic archives in the region. The REEs in the Fe-Mn oxyhydroxides support the argument of water mass signature separation in bulk sediments by chemical leaching procedures. These 87Sr/86Sr in the Fe-Mn oxyhydroxides phase fall in a range between 0.709262 and 0.709313, deviating significantly from the modern seawater. ƐNd values vary >3Ɛ, being more radiogenic in the Fe-Mn oxyhydroxides, where the lowest value occurred in the Bølling/Allerød (B/A) and higher values occurred during the Younger Dryas (YD). The latter implies increased contribution of loess dusts or Taiwanese rivers under dry/cold climatic conditions, compared with the situation in modern times. The Red River and the Mekong River together may have contributed >60% during the Last Glacial Maximum (LGM) and YD. In contrast, the Pearl River components have increased sharply to 60% during the warm B/A. These results demonstrate that the MD05-2901 sediments sensitively record changes in weathering intensity on land and transport pathways in the coastal regions in the Holocene.